Simulasi Monitoring Ketinggian Air Danau dan Kontrol Pompa Air Menggunakan Modul Arduino di Bandara Internasional Juanda Surabay - Hartono Hartono; Wempy Brilliansya (Jurnal Penelitian)
Overflow of lakes can be occured in Juanda International Airport at rainy season because the pump is too late to flow water into the river. To solve this problem, the technician must come to the location to check the water level and operates the pump. The operation of the pumps by technicians is not effective because there is no automatic control and Human Machine Interface system in PC. whilethe distance from the technician room to the Pump House is far enough and costed time to reach the place. Due to the situation, the writer designed an automatic control water pump and monitoring water level of lake and river with arduino module. Ultrasonic sensor HC-SR04 is used to determine the water level and control the pumps. Current sensor ACS-712 detects the current from the pumps. After the water level and current for the pump is determined the results will be displayed in PC using visual basic as human main interface.